2018
DOI: 10.3920/cep180004
|View full text |Cite
|
Sign up to set email alerts
|

Airway endoscopy and tracheal cytology of two-year-old Thoroughbred horses during the first year of race training

Abstract: The immunological status of the respiratory tract is critical to racehorses’ performance. Respiratory diseases in young Thoroughbred (TB) racehorses are a major concern during their early athletic career. This study investigated the airway adaptations occurring in young TB race horses during their first year of race training. Eighteen animals were evaluated at five different time points over a one-year follow-up period. A physical examination was performed, followed by airway endoscopy, in which tracheal mucus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Considering a cutoff of 25% of neutrophils in the TW cytology, the study of Almeida et al (2018) investigated a group of 18 TB racehorses. Sixty days after entering training, they found that the mean neutrophil count was higher than 27%.…”
Section: Tracheal Wash (Tw)mentioning
confidence: 99%
“…Considering a cutoff of 25% of neutrophils in the TW cytology, the study of Almeida et al (2018) investigated a group of 18 TB racehorses. Sixty days after entering training, they found that the mean neutrophil count was higher than 27%.…”
Section: Tracheal Wash (Tw)mentioning
confidence: 99%